Particulate matter measurement by using the particle sizers APS and SMPS - Holubčík, M.; Jandačka, J.; Ďurčanský, P.; Čaja, A. (EAI Endorsed Transactions on Energy Web, 2020)
Currently, there is an increasing trend in the use of biomass for energy purposes, due to global pressure on the use of renewable energy sources and a gradual decline in fossil fuel stocks. However, biomass combustion can be considered as a significant source of particulate concentrations in the atmosphere. Measurement of particles from biomass combustion plants is very demanding; the particle size range is large, usually ranging from a few nanometers (nm) to a few micrometers (μm). The measurement of the particles is carried out in terms of mass concentrations, numerous concentrations and their particle size distribution. The selection of metering devices for measuring particulate matter and their size distribution is important because different devices differ in their characteristics and have specific advantages and disadvantages. The large particle number concentrations in the flue gas after biomass combustion exceed the detection capacity of some plants, therefore they are used for measurement with flue gas diluents for measurement. At present, the gravimetric method, the method of particulate matter measuring using an aerodynamic particle sizer (APS) or a scanning mobility particle sizer (SMPS) is often used. The cascade impactor gravimetric method is based on comparing particles basedon their aerodynamic diameter. APS is a spectrometer that measures particles between 0.5 and 20 μm in size. The working principle is based on the acceleration of aerosol sample flow through an accelerating orifice. SMPS measures the size distribution and concentration of particles in the size range of 1 nm to 1 μm using differential mobility analysis. When the device SMPS is used with the APS, the range increases to 20 μm. This paper focuses on the measurement of particulate matter by tandem connection of APS and SMPS particle sizers using dilution. Dilution is used to eliminate the mechanisms that arise when sampling particles that may affect their properties. These are nucleation, condensation, evaporation and coagulation. The results are then compared with gravimetric measurements.
Keywords: particulate matter; particle sizer; gravimetric method; APS; SMPS